The reference intervals for biochemistry analytes obtained through the indirect method indicate the metabolic shifts in the Thai adult population - Kongkhum, Sudawadee; Sarnkhaow, Sopawan (Journal of Associated Medical Sciences, 2025)
Background: Reference intervals (RIs) of biochemistry analytes are required to make medical decisions. According to the standards, medical laboratories shall validate and/or verify RI for their own uses because there are biological and laboratory variations. Objective: To determine RIs of 14 biochemistry analytes, including fasting blood glucose, total cholesterol, HDL cholesterol, triglyceride, total protein, albumin, BUN, creatinine, uric acid, AST, ALT, ALP, amylase, and lipase in Thai adults. Materials and methods: RIs were determined by using the indirect method. Test results from 18 years old or older out-patient department patients were collected from the hospital laboratory database from January 2019 to December 2021. The results from subjects with a high likelihood of disease were excluded, outliers were removed, data distribution was tested, and RIs were determined as either mean±2SD or the 2.5th to 97.5th percentile for normal and non-normal distribution data, respectively. Results: There were 197,897 test results available for RI determination. Most of the determined RIs were comparable to those from the manufacturer, except uric acid. All 14 RIs passed verification criteria in the population served. Interestingly, our RIs for blood total cholesterol, triglyceride, and uric acid were higher than those established in the previous reports in Thai population. Conclusion: The RIs were established and verified in Thai adults; therefore, they could be implemented for the population. In addition, our RIs of total cholesterol, triglyceride, and uric acid reflect metabolic changes of the studied population.